One carbon metabolism supplementation in maturation medium but not embryo culture medium improves the yield of blastocysts from bovine oocytes - Arefeh Golestanfar; Amir Niasari Naslaji; Farnoosh Jafarpour; Nima Sadeghi Borujen; Shiva Rouhollahi Varnosfaderani; Yves Menezo; Maurizio Dattilo; Mohammad Hossein Nasr-Esfahani (Scientific Reports)
Abstract Optimizing oocyte maturation and embryo culture media could enhance in vitro embryo production. The purpose of the present study was to investigate the role of supplementing one carbon metabolism (OCM) substrates and its cofactors (Cystine, Zinc, Betaine, B2, B3, B6, B12 and 5-methyltetrahydrofolate) in maturation and/or embryo culture media on the rate of blastocyst formation and pregnancy outcomes following the transfer of the resulting blastocysts in bovines. In the first experiment, 2537 bovine oocytes were recovered from slaughterhouse ovaries and then matured either in conventional maturation medium (IVM) or IVM supplemented with OCM substrates (Sup-IVM). After in vitro fertilization, the putative zygotes from each treatment (IVM or Sup-IVM) were cultured in the media either without (IVM/IVC or Sup-IVM/IVC) or with (IVM/Sup-IVC or Sup-IVM/Sup-IVC) OCM supplementation. The blastocyst rate, assessed on day 8, was significantly increased in Sup-IVM/IVC group (34.90 ± 2.52) as compared to IVM/IVC (17.06 ± 1.69; P = 0.0001) and Sup-IVM/Sup-IVC (20.29 ± 2.75; P = 0.004) and non-significantly as compared to IVM/Sup-IVC (24.86 ± 5.37). In the second experiment, non-matured bovine oocytes were collected by transvaginal ovum pick up after FSH stimulation, randomly allocated into IVM/IVC (n = 275) and Sup-IVM/IVC (n = 260) and the blastocysts achieved at day 7 were transferred in recipient cattle. The blastocyst rate was significantly higher in Sup-IVM/IVC group (38.85%) as compared to the IVM/IVC group (23.64%; P < 0.0001). After single embryo transfer, the supplemented blastocysts were at least as competent as non-supplemented ones with a non-significantly higher (20% vs. 14%) pregnancy rate and the advantage of several good quality blastocysts available for future use. In conclusion, optimizing the maturation medium with OCM substrates and its cofactors could enhance the formation of viable blastocysts with the potential to increase the cumulative birth rate in cattle.